2012
DOI: 10.1364/ao.51.004394
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a noncontacting, white light Fabry–Perot interferometric displacement sensor

Abstract: A white light extrinsic Fabry-Perot interferometer is implemented as a noncontacting displacement sensor, providing robust, absolute displacement measurements with micrometer accuracy at a sampling rate of 10 Hz. This paper presents a dynamic model of the sensing cavity between the sensor probe and the nearby target surface using a Fabry-Perot etalon approach obtained from straightforward electromagnetic field formulations. Such a model is important for system characterization, as the dynamically changing cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…4 (with the velocity still assumed unknown for the moment). Using the experimental parameters determined in this problem, with f 0 = 1.935×10 14 Hz, ∆f 0 = 9.993×10 12 Hz (corresponding to an 80 nm filter sweep), and ∆t = 40 ms, L b = −0.77v, which is extremely close to the results presented in [4].…”
Section: B Interferogram Decompositionsupporting
confidence: 83%
See 1 more Smart Citation
“…4 (with the velocity still assumed unknown for the moment). Using the experimental parameters determined in this problem, with f 0 = 1.935×10 14 Hz, ∆f 0 = 9.993×10 12 Hz (corresponding to an 80 nm filter sweep), and ∆t = 40 ms, L b = −0.77v, which is extremely close to the results presented in [4].…”
Section: B Interferogram Decompositionsupporting
confidence: 83%
“…3, a comparison between the actual (independently known) DUT position and the estimated DUT position clearly shows a bias, manifesting itself in an apparent jump in the DUTs estimated position when there is non-zero DUT velocity. The right-hand side of the figure shows a sample cepstrum comparison between the static and dynamic cases for the specific velocity of 5 mm/s; in [4], it was shown that even a DUT velocity of 0.1 mm/s resulted in a relatively large 64 µm bias in the position. Errors of this magnitude can severely limit sensor performance.…”
Section: Broadbandmentioning
confidence: 99%
“…In spite of these advantages, the authors recently observed that white light EFPI position sensors are highly sensitive to DUT velocity, where any DUT motion was shown in [9] to impart a Doppler shift on the signal circulating within the Fabry-Perot sensing cavity (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…2). More specifically, in the research performed in [9], the authors utilized a PXIe-4844 optical interrogator (National Instruments Inc.), which consists of a broadband InGaAs source, a swept filter that tunes over the 1510-1590 nm wavelength range in 0.04 s with an absolute wavelength accuracy of 1 pm (which relates to the filter's linearity), wavelength referencing hardware, a broadband photodetector, and circulators, all arranged similarly to the generic diagram shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation